Effect of Heat Treatment on Storage Stability of Sheep Tail Fat - Bozdemir, M.; Gençcelep, H.; Yuzer, M.O. (Sidas Medya A.Ş., 2024)
In this study, the effects of various physical, chemical, and technological properties of sheep tail fat (fresh and ghee) as well as different storage durations, storage temperatures, and the use of additives on the storage stability of thermally processed sheep tail fat (ghee tail fat) were investigated. To prevent lipid oxidation and other degradation factors during use after long-term storage, salt and antioxidant additives were used. Samples were stored in glass jars at 25ºC, +4ºC, and -18ºC for 90 days. The moisture, protein, fat, and ash contents of fresh tail fat was determined as 11.2%, 3.47%, 85.0%, and 0.07%, respectively. In clarified fat, the moisture content was determined as 0.4%, protein content as 2.98%, fat content as 96.0%, and ash content as 0.05%. Additionally, the cholesterol content in tail fat was 60 mg/100 g in fresh tail fat and 58 mg/100 g in ghee tail fat. The pH values of fats were determined as 5.7 in fresh samples and 6.2 in ghee samples. The fatty acid compositions of samples revealed that the dominant fatty acid groups in both fresh and ghee sheep tail fat were palmitic, stearic, and oleic acids. Fresh tail fat stored at room temperature deteriorated in terms of chemical properties (FFA, peroxide, and TBA) within 7 days, while those stored at +4ºC deteriorated within 15 days. However, thermally processed samples were preserved without deterioration for 60 days at these storage temperatures. © 2024 Sidas Medya A.S.. All rights reserved.
Isıl İşlemin Koyun Kuyruk Yağının Depolama Stabilitesi Üzerine Etkisi
Keywords: Animal Fat; Sheep Tail Fat; Storage Stability; Tallow